Comparative Study of Different Growing Media and Bioagent Applications on Growth and Survival of Mango Grafts (Mangifera indica L.) cv. Kesar - Ambrish, S.; Lohakare, A. S.; Sasane, P. A. (International Journal of Bio-resource and Stress Management, 2025)
An investigation was carried out during the period from June, 2021 to February, 2022 at the College of Horticulture, Vasantrao Naik Marathwada Krishi Vidyapeeth, Parbhani, Maharashtra (431 402), India, to study the effect of different growing media and bioagent applications on the growth and survival of mango grafts (Mangifera indica L.) cv. Kesar. The experiment was laid out in a Randomized Block Design (RBD) with thirteen treatments replicated thrice. The treatment combination of Orchard soil, Farm Yard Manure (FYM), and Vermicompost (1:1:1) with Biomix 1% showed a significant increase in the height of grafts (24.24 cm, 28.25 cm, 31.38 cm, and 34.33 cm), length of scion (16.75 cm, 20.16 cm, 23.39 cm, and 24.58 cm), number of leaves (7.33, 10.72, 13.78, and 15.69), and leaf area (13.36 cm², 19.75 cm², 23.56 cm², and 28.79 cm²) at 30, 60, 90, and 120 days after grafting (DAG), respectively. The same treatment also recorded the highest survival percentages (87.06%, 83.17%, 78.33%, and 74.31%) at 30, 60, 90, and 120 DAG, respectively. Moreover, it resulted in the minimum number of days required for sprouting (10.52 days) and the highest success percentage (74.31%), as well as the maximum root length (24.60 cm), fresh and dry weights of roots (14.38 g and 8.78 g, respectively), and fresh and dry weights of shoots (24.53 g and 17.25 g, respectively) at 120 DAG. This indicates that the media combination of orchard soil, FYM, vermicompost (1:1:1) with Biomix 1% is highly effective in promoting the growth and survival of mango grafts.